The Education of Noblewomen in Early Modern Hungary Through the Example of Judith Balassa (Theatrum historiae, 2025)
The early modern period witnessed an increase in women’s writing as a result of the significant spread of literacy. Among the sources of a personal nature, correspondence is the most useful for research, especially the letters of the nobility, as these are the most widespread and thus the most accessible type of egodocuments from this period. The constant threat from the Ottoman presence in East-Central Europe meant that men were frequently away from home, whether for military or political reasons, and so the agenda of looking after the family estate fell into the hands of women. Being able to read, write, and do basic mathematics thus became a necessity for women to be adequately able to look after the family estates. The paper deals with the issue of women’s education in the early modern period on the basis of an analysis of the correspondence of Baroness Judith Balassa (c. 1630–c. 1685), the second wife of Stephen I. Koháry (1616–1664), who, after his sudden death, had to take care of the family property and provide for her descendants. The paper examines the matter of the education and upbringing of noble girls in this period. Subsequently, the educational level of Judith Balassa is characterised by analysing her written expression and comparing it with that of other literate aristocratic women. Alongside this, attention is also paid to the question of the linguistic competence of Judith Balassa and her closest family members.
Keywords: Upbringing and Education of Women; Literacy; Nobility; Aristocracy; Early Modern Period